2015
DOI: 10.1016/j.bmcl.2015.05.035
|View full text |Cite
|
Sign up to set email alerts
|

Fully automated synthesis of [18F]T807, a PET tau tracer for Alzheimer’s disease

Abstract: Abstract-The authentic standard T807 and its nitro-precursor T807P as well as t-Boc-protected T807P precursor for radiolabeling were synthesized from (4-bromophenyl)boronic acid, 3-bromo-4-nitropyridine and 3-bromo-6-nitropyridine with overall chemical yield 27% in three steps, 4-7% in three to five steps, and 3-8% in four to five steps, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…Issues with solubility of the nitro-precursor have been partially resolved by N-Boc protection of the carbazole nitrogen, which improves solubility by increasing the lipophilicity of the molecule. Literature reports are unclear as to whether N-Boc protection improves radiochemical conversion or if increased yields are due to the solubility afforded (Shoup et al 2013 ; Gao et al 2015 ). Ambiguity also surrounds the deprotection of N-Boc-protected [ 18 F]AV1451 in the literature: Shoup and Gao describe the N-Boc group being removed concomitantly with fluorination through either thermal promotion or due to the basic reaction conditions (Shoup et al 2013 ; Gao et al 2015 ), while Holt and co-workers add HCl following fluorination to deprotect in a separate deprotection step (Holt et al 2016 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Issues with solubility of the nitro-precursor have been partially resolved by N-Boc protection of the carbazole nitrogen, which improves solubility by increasing the lipophilicity of the molecule. Literature reports are unclear as to whether N-Boc protection improves radiochemical conversion or if increased yields are due to the solubility afforded (Shoup et al 2013 ; Gao et al 2015 ). Ambiguity also surrounds the deprotection of N-Boc-protected [ 18 F]AV1451 in the literature: Shoup and Gao describe the N-Boc group being removed concomitantly with fluorination through either thermal promotion or due to the basic reaction conditions (Shoup et al 2013 ; Gao et al 2015 ), while Holt and co-workers add HCl following fluorination to deprotect in a separate deprotection step (Holt et al 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Reflecting its widespread use, several different syntheses of [ 18 F]AV1451 suitable for clinical use have been reported. Shoup and Gao both reported syntheses of [ 18 F]AV1451 from N-Boc-protected nitro precursor (Shoup et al 2013 ; Gao et al 2015 ), which eliminated the need for the reduction of the nitro precursor prior to purification that the original report required to facilitate purification of [ 18 F]AV1451 (Xia et al 2013 ). More recently, Holt et al reported 18 F-fluorination of N-Boc-protected trimethylammonium precursor by microwave irradiation (Holt et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This “in‐loop” [ 18 F]fluorination methodology was then applied for the syntheses of [ 18 F]T807 and [ 18 F]FEPPA (Table ). The synthesis of [ 18 F]T807 has previously been reported by several research groups in RCYs ranging from 14% to 32%. [ 18 F]T807 is commonly produced via our two‐step one‐pot procedure, which entails firstly the nucleophilic 18 F‐fluorination of the nitro‐ or tetramethylammonium‐based precursor compound, followed by thermal Boc deprotection to form the desired product.…”
Section: Resultsmentioning
confidence: 99%
“…The most notable of these is Pittsburgh compound B which binds deposits of Ab, allowing for PET imaging of pathology in living individuals [29]. Several PET tracers are also in development for tau imaging [30][31][32][33]. Levels of total tau and Ab in the CSF show alteration early in their disease course (increasing and decreasing respectively) [34] and certain tau phosphoepitopes (Thr181 and Thr213) [35][36][37][38] in the CSF may be indicative of disease, although these tests require a lumbar puncture.…”
mentioning
confidence: 99%